An industrial‐organization approach to conventional and unconventional monetary policy. (14th June 2021) - Gunji, Hiroshi; Miyazaki, Kenji
Abstract: In this study, we use an industrial‐organization model of the banking industry with money creation to examine the effect of conventional and unconventional monetary policy on the money stock. We consider quantitative monetary easing, qualitative monetary easing, and a negative interest rate on excess reserve balances as unconventional monetary policy. Our main findings are as follows. First, under a plausible setting of the parameters, the model with money creation supports the liquidity puzzle, in which tight monetary policy increases the money stock. The greater the number of banks, the stronger the effect. Second, quantitative monetary easing has no impact on money stocks, loans, deposits and bank holding assets other than government bonds. Third, the effect of qualitative monetary easing is ambiguous, but when the number of banks is sufficiently large, the effect is almost the same as the interest rate on reserves. Fourth, the effect of negative interest rate policy is quite complex.